A composite hydrogel for brain tissue phantoms. (15th December 2016) - Forte, Antonio E.; Galvan, Stefano; Manieri, Francesco; Rodriguez y Baena, Ferdinando; Dini, Daniele
Abstract: Synthetic phantoms are valuable tools for training, research and development in traditional and computer aided surgery, but complex organs, such as the brain, are difficult to replicate. Here, we present the development of a new composite hydrogel capable of mimicking the mechanical response of brain tissue under loading. Our results demonstrate how the combination of two different hydrogels, whose synergistic interaction results in a highly tunable blend, produces a hybrid material that closely matches the strongly dynamic and non-linear response of brain tissue. The new synthetic material is inexpensive, simple to prepare, and its constitutive components are both widely available and biocompatible. Our investigation of the properties of this engineered tissue, using both small scale testing and life-sized brain phantoms, shows that it is suitable for reproducing the brain shift phenomenon and brain tissue response to indentation and palpation. Graphical abstract: Highlights: Design and development of a composite hydrogel to mimic brain tissue Testing, material characterisation and comparison with brain tissue Manufacturing and testing of life-size phantom Optimisation of mechanical response of the composite hydrogel